An approach to determine enthalpies of formation for ternary compounds - Du Y.; Wang J.; Ouyang Y.F.; Zhang L.J.; Yuan Z.H.; Liu S.H.; Nash P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
An integrated approach of experiment and theoretical computation to acquire enthalpies of formation for ternary compounds is described. The enthalpies of formation (DHf ) for Al71Fe19Si10 and Al31Mn6Ni2 are measured via a calorimeter. Miedema model, CALPHAD and first-principles method are employed to calculate DHf for the above compounds and several Al-based ternary compounds. It is found that first-principles generated data yield good agreements with experimental values and thus can be used as key 'experimental data', which are needed for CALPHAD approach.